Analysis of the human resources development scenario and the employability prospects for the next years in the oil and gas area in Brazil and the development of a didactic test bench for the simulation of oil well drilling operations. - Pedro, Beatriz Maciel Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The fossil fuels still are the world’s main energy source and will continue being in the next years. In this day, it is extremely important to assure an qualified and specialized manpower in the sector. The paper consists of an analysis of the human resources development scenario in the area of Oil and Gas in Brazil, through the analysis of people management, the existence of manpower and the need for its qualification. In addition to an analysis of the prospects for employability scenario in the sector by means of a discussion about the historical context of the employability scenario. Data regarding graduation and post-graduation courses related to Oil and Gas were analyzed, in relation to the profile of vacancies and the institutions that offer them. Additionally, were discussed historical events that have influenced the oil price per barrel and related to the population interest in taking courses related to the area in question. Finally, were also analyzed ways for companies and research centers to invest in the qualification of manpower in the sector by means of partnership with universities through human resources development programs with the aim of encouraging students to specialize in the area.

Os combustíveis fósseis ainda são a principal fonte de energia mundial e continuarão sendo nos próximos anos. Dessa forma, se faz de vital importância a preocupação em garantir uma mão de obra qualificada e especializada no setor. O trabalho consiste em uma análise do cenário de formação de recursos humanos na área de petróleo e gás no Brasil, por meio da análise da gestão de pessoas, da existência de mão de obra e da necessidade de sua qualificação. Além de uma análise das perspectivas de empregabilidade no setor por meio da discussão do contexto histórico do cenário de empregabilidade no mesmo. Foram analisados dados relativos à cursos de graduação e pós graduação relacionados à petróleo e gás, em relação ao perfil das vagas e instituições que os oferecem. Também foi discutido acontecimentos históricos que exerceram influência nos valores dos preços do barril do petróleo e relacionado com o interesse por parte da população em cursar os cursos relacionados à área. Por fim, também foram analisadas formas de investimento na qualificação da mão de obra no setor por parte de empresas e de centros de pesquisa em parceria com universidades por meio de programas de formação de recursos humanos com o objetivo de incentivar os alunos a se especializarem na área.
Análise do cenário de formação de recursos humanos e perspectivas de empregabilidade para os próximos anos na área de óleo e gás no Brasil e desenvolvimento de uma bancada didática de testes para a simulação de operações de perfuração de poços petrolíferos.
Keywords: Fossil Fuel; Manpower; Drilling Simulation; Combustíveis Fósseis; Mão de Obra; Simulação de Perfuração